Acid soil management in north eastern hill region of India - Majumdar, Sabyasachi; Wanniang, Samborlang K; Behera, Umakanta (Indian Farming, 2022)
Acid soil is dominant in North-Eastern Region (NER) of India comprising 26.22 million hectaresout of which 21.26 million hectares is affected by soil acidity. Distribution of acid soil in North-Eastern Hill (NEH) region varies from 80–100%. Acid soil is deficient in P, Ca, Mg, Mo andB, and as a result limits crop growth and yield to varying extent. Management of acid soil isimportant to enhance the productivity of the soil and performance of the crops. Soil amendedmentwith lime, growing tolerant crops and varieties, organic amendments, viz. poultry manure, farm yard manure, pig manure, green manures and biochar, good agronomic practices, adoption of agroforestry are the promising practices suitable for enhancing the productivity of acid soils. Central Agricultural University (CAU) gave way to a new centre for research on acid soil management. The goal is to make CAU a scientific leader in natural agriculture by providing and implementing innovative approaches and game changer technologies such as natural farming, advanced research on organic farming, integrated farming system, acid soil management, and rice-fallow systemproduction.